The interplay between sex, lifestyle factors and built environment on 20-year cardiovascular disease incidence; the ATTICA study (2002–2022) - Sigala, Evangelia G.; Chrysohoou, Christina; Barkas, Fotios; Liberopoulos, Evangelos; Sfikakis, Petros P.; Faka, Antigoni; Tsioufis, Costas; Pitsavos, Christos; Panagiotakos, Demosthenes (Frontiers in Cardiovascular Medicine, 2025)
Background and aimThis study aims to investigate the role of the built environment in terms of urban-rural disparities in cardiovascular disease (CVD) epidemiology, focusing on middle- and long-term CVD risk assessment. Moreover, this study seeks to explore sex-specific differences in urban and rural settings.MethodsThe ATTICA Study is a prospective study conducted from 2002 onwards. At baseline, a random sample of 3,042 CVD-free adults (49.8% men) were randomly drawn from the population of the Attica region, in Greece, with 78% dwelling in urban and 22% in rural municipalities. Follow-up examinations were performed in 2006, 2012, and 2022. Of the total participants, 1,988 had complete data for CVD assessment in the 20-year follow-up.ResultsThe 10-year and 20-year CVD incidence was 11.8%, 28.0% in rural municipalities and 16.8%, 38.7% in urban municipalities, respectively (ps < 0.05). Unadjusted data analyses revealed significant differences in clinical, laboratory, and lifestyle-related CVD risk factors between urban and rural residents (ps < 0.05). Additionally, sex-based discrepancies in clinical, anthropometric, circulating, and lifestyle risk factors were observed in stratified analyses of urban and rural settings. Multivariate analyses, including generalized structural equation modeling (GSEM), revealed that the impact of the urban built environment on the long-term (20-year) CVD risk is mediated by lifestyle-related risk factors.ConclusionUrban inhabitants exhibit a higher long-term CVD incidence compared to their rural counterparts, which was partially explained by their lifestyle behaviors. Targeted strategic city planning efforts promoting healthier lifestyle-related behaviors at the micro-environment level could potentially mitigate built-environment impacts on CVD health.